Gênero e efetividade da terapia de manutenção entre pacientes transplantados renais, no Brasil, no período de 2001 a 2006: uma coorte histórica - Erika Vieira de Almeida (2014)
Introduction: Renal Therapy (RT) aims to reduce rejections and substantially increase graft survival in renal transplant recipients. However, the pre-operative differences can influence treatment. Objectives: To analyze the differences between genders of the baseline characteristics and the monitoring clinical effectiveness results (graft and patient survival) in maintenance renal transplant recipients enrolled in the Unified Health System (SUS) therapy Methods: This study presents two components. At first, we conducted a systematic literature review with the aim of exploring the theme gender differences related to renal transplant (RT), focusing on clinical and demographic baseline indicators (pretransplant) and clinical outcome (post-transplant) in terms of treatment effectiveness. We conducted a search for articles on observational studies, cohort trials, published up to December 2013 in MEDLINE (PubMed) and Latin American Literature data and Caribbean Health Sciences (LILACS) and the Cochrane Controlled Trials and NHS Centre for Reviews and Dissemination databases. Specifically in relation to pre-transplant characteristics, we analyzed gender differences in receptors, kidney donors or in both. The outcomes assessed in the meta-analysis were graft and patient survival, by follow-up (1st year, 2nd year, 3rd year, 5th year, 8 years and 10 years). We used the Newcastle-Ottawa scale to assess the methodological quality of the studies. Statistical analysis was performed using Review Manager Metaview module version 5.2.11 software. The results were presented as relative risk (RR) and its heterogeneity were analyzed using the chi-square and I2 statistics. In the second component, we performed a historical cohort study, among 2001 and 2006, in adult patients undergoing kidney transplantation and who made use of immunosuppressive drugs supplied by the Specialized Component of Pharmaceutical Assistance (azathioprine, cyclosporine, mycophenolate sodium, mycophenolate mofetil, sirolimus and tacrolimus). Participants were identified through probabilistic linkage of administrative data from hospital information (SIH / SUS), outpatient (APAC / SIA) and mortality (SIM) systems. Analyzes were stratified by gender for selected characteristics, using chi-square, Student's t or Mann-Whitney tests. To estimate the cumulative probability of patient and graft survival, we used non-parametric Kaplan-Meier method. Comparison of the curves for different subgroups, male and female, was based on the log-rank test significance level and for all analyzes was considered the value of 0.05. Results: i. Systematic literature review: 30 studies were included and the results were organized according to the recipient gender, the donor gender and donor gender and TR receiver at the same time in different combinations. We observed worse graft and patient survival for the combination - female donor to male recipient. ii. Historical cohort: 19,726 patients, 11,131 (56.4%) males were included. Predominated the initial use of cyclosporine and mycophenolate for both men and women. At 72 months of follow-up, the overall rate of graft and patient survival, was, respectively, 94.9% and 90.8%. There were significant differences for age, region of birth, year of transplantation and immunosuppressive therapy. The rate of graft survival was 95.2% and 94.6% respectively for men and women, without statistical significance. The survival rate was 91.7% and 90.1%, respectively, for men and women (p <0.000). Conclusion: The results of the systematic review and analysis of the historical cohort characteristics by sex, showed statistically significant differences between men and women. Better assessment of patients' risk profiles by gender may offer the opportunity for greater individualization of immunosuppression after renal transplantation.